Seismic Analysis and Design Using the Endurance Time Method : Concepts and Development. - Estekanchi, Homayoon (Momentum Press, 2018)
A new approach to seismic assessment of structures called endurance time method (ETM) is developed. ETM is a dynamic analysis procedure in which intensifying dynamic excitations are used as the loading function. ETM provides many unique benefits in seismic assessment and design of structures. ETM is a response history-based procedure. ETM considerably reduces the computational effort needed in typical response history analyses. Conceptual simplicity makes ETM a great tool for preliminary response history analysis of almost any dynamic structural system. Most important areas of application of ETM are in the fields of seismic design optimization, value-based seismic design, and experimental studies. This book is aimed to serve as a coherent source of information for students, engineers, and researchers who want to familiarize themselves with the concepts and put the concepts into practice.